CALPUFF와 HYSPLIT의 방사성물질 대기확산 특성 비교 - 안혜연(Hye Yeon An); 강윤희(Yoon-Hee Kang); 송상근(Sang-Keun Song); 김유근(Yoo-Keun Kim) (한국대기환경학회지, 2015)
In this study, the atmospheric dispersion of radioactive material ($^{137}Cs$) was simulated with regard to its impact within a 50-km radius from the Kori Nuclear Power Plant (NKPP) based on two different types of models (the non-steady-state puff model CALPUFF and the lagrangian model HYSPLIT) during the spring of 2012 (May 2012). The dispersion distribution of $^{137}Cs$ calculated in the CALPUFF model was similar to that of the HYSPLIT model, but the magnitudes of differences in its spatio-temporal concentrations between the two models were different. The $^{137}Cs$ concentrations simulated by the CALPUFF were significantly lower than those of the HYSPLIT due to a limitation of puff models (e.g. puff size growth over time). The CALPUFF had the advantage of determining the dispersion of radioactive materials and their impacts on the surrounding regions, compared with the HYSPLIT that had high concentrations of $^{137}Cs$ in only small local areas with the movement of air masses along the local winds.